Hybridization and accumulation of space-heating systems in Finnish detached housing - Sini Numminen; Marika Silvikko de Villafranca; Sampsa Hyysalo (Energy Strategy Reviews, 2024)
The uptake of renewable energy sources is intensifying in detached houses in the Nordic countries. Survey results (N = 4276) among a detached-house owner association members in Finland imply that the energy transition has progressed further than believed. In the sample, 89 % of households had two or more systems which suggests an accumulation and parallel use of heating systems instead of removing older energy technologies. The phenomenon concerns houses with electric heating, wood heating and air-source heat-pumps, and the owner-occupant sample is rather even across socio-demographic backgrounds. However, larger homes had a higher number of energy technologies, and hybrid arrangements were also adopted more by male respondents. Women, unemployed, and families with three members or more had higher odds for relying only on one energy technology or fuel. The results call for urgent updates in European energy statistics and classifications and the energy policy measures targeted at residential sector, both from energy justice and heating decarbonization perspectives. This is one of the rare studies focusing on hybridization of residential heating in Nordic countries.